2020
DOI: 10.1101/2020.04.01.20050476
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Case fatality rate in COVID-19: a systematic review and meta-analysis

Abstract: Background: Estimating the prevalence of severe or critical illness and case fatality of COVID-24 19 outbreak in December, 2019 remains a challenge due to biases associated with surveillance, 25 data synthesis and reporting. We aimed to address this limitation in a systematic review and 26 meta-analysis and to examine the clinical, biochemical and radiological risk factors in a meta-27 regression. 28Methods: PRISMA guidelines were followed. PubMed, Scopus and Web of Science were 29 searched using pre-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 50 publications
0
21
0
1
Order By: Relevance
“…This retrospective study of the risk of COVID-19 infection identified several clinical risk factors also associated with serious illness in prior studies, including older age [3], male gender [15], diabetes [7], chronic kidney disease [16], high BMI [17], and immunosuppression [18]. However, some factors previously found to increase mortality risk, such as hypertension [3], and cardiovascular disease, liver disease, lung disease, or asthma [8], were not significant factors associated with initial COVID-19 infection.…”
Section: Clinical Risk Factorsmentioning
confidence: 92%
See 2 more Smart Citations
“…This retrospective study of the risk of COVID-19 infection identified several clinical risk factors also associated with serious illness in prior studies, including older age [3], male gender [15], diabetes [7], chronic kidney disease [16], high BMI [17], and immunosuppression [18]. However, some factors previously found to increase mortality risk, such as hypertension [3], and cardiovascular disease, liver disease, lung disease, or asthma [8], were not significant factors associated with initial COVID-19 infection.…”
Section: Clinical Risk Factorsmentioning
confidence: 92%
“…While statistical models have been built to predict severity of illness and mortality related to COVID-19 infection [1], less has been done to predict the risk of initial infection in community settings. Studies to date have contained limited demographic information, have focused on hospitalized patients, and have not been representative of U.S. populations [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 chronic kidney disease, 16 high BMI, 17 and immunosuppression. 18 However, some factors previously found to increase mortality risk, such as hypertension, 3 and cardiovascular disease, liver disease, lung disease, or asthma, 8 were not signi cant factors associated with initial COVID-19 infection.. Surprisingly, being prescribed more than ten medications or having a greater number of chronic conditions was associated with less infection risk, suggesting possible risk reduction behavior based on perceived risk.…”
Section: Prediction Of Infection Riskmentioning
confidence: 94%
“…In total, 25 health conditions were identified with COVID-19 vulnerability and/or complications, reported by two guidelines, 15 , 20 16 published reviews 5 , 25 – 28 , 30 – 33 , 54 , 61 – 66 and 10 preprint reviews. 37 , 39 , 42 , 45 , 47 , 57 , 59 , 60 , 67 , 68 The list of conditions included the ’high-risk‘ or ’extremely vulnerable from COVID-19’ criteria based on guidelines issued by Public Health England and Health Protection Scotland. 69 , 70 The list included a breadth of conditions ranging from cardiovascular, respiratory, immunosuppressed conditions, and previous cancer (see Table 2 for the list of medical conditions and the proposed examples of corresponding SNOMED CT codes).…”
Section: Resultsmentioning
confidence: 99%